2014
DOI: 10.1680/warm.13.00031
|View full text |Cite
|
Sign up to set email alerts
|

A case study of the D4R laptop

Abstract: The D4R (Design for recycling, repair, refurbishment and reuse) laptop was developed in conjunction with MicroPro Computers (MPC), a Dublin-based computer manufacturer. MPC formed an industrial network with end-of-life information technology (IT) asset management firms, IT refurbishers, component manufacturers and local industries to produce a new design that has created a new use for their wastes, thus turning waste into resources. This has been made possible through: D4R product design features that facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…in a case of construction and demolition waste (Chen et al 2006)). The challenge often is to bootstrap such systems, such as in The Resource eXchange Platform (TRXP) (Dietrich et al 2014;Hickey et al 2014), a resource 'exchange' web-platform facilitating industrial symbiosis by building a network of organizations in Europe that could reuse or disassemble industrial streams of ICT equipment. The researchers (Dietrich et al 2014) show that the open platform is technically feasible and could extend reuse streams by means of industrial symbiosis.…”
Section: Open Online Waste Marketsmentioning
confidence: 99%
“…in a case of construction and demolition waste (Chen et al 2006)). The challenge often is to bootstrap such systems, such as in The Resource eXchange Platform (TRXP) (Dietrich et al 2014;Hickey et al 2014), a resource 'exchange' web-platform facilitating industrial symbiosis by building a network of organizations in Europe that could reuse or disassemble industrial streams of ICT equipment. The researchers (Dietrich et al 2014) show that the open platform is technically feasible and could extend reuse streams by means of industrial symbiosis.…”
Section: Open Online Waste Marketsmentioning
confidence: 99%
“…Already the waste in context with the production is reduced, partly by the idea, that waste of the production becomes a resource for another company's production. Additionally, the product design aims to extend the life span of the laptop to a mimimum of 10 years [39].…”
Section: Ecological Product Designmentioning
confidence: 99%
“…Two of the Zerowin case studies apply this methodology for high-tech products: a laptop and a photovoltaic (PV) system. The D4R laptop case study (Hickey et al, 2014) has demonstrated an industrial network established by a laptop manufacturer MicroPro with end-of-life IT asset management firms, IT refurbishers, component manufacturers and local industries. The innovative idea was to develop a laptop design that allows the creation of a new life for the used IT components, thus turning wastes into products.…”
mentioning
confidence: 99%